Expanded ro–vibrational analysis of the dyad region of CD4: Line positions and energy levels. (September 2022) - Bauerecker, S.; Sydow, C.; Maul, C.; Gromova, O.V.; Bekhtereva, E.S.; Nikolaeva, N.I.; Ulenikov, O.N.
Highlights: The v 2 and v 4 interacting bands of CD4 Resonance interactions in spherical top molecules. Determination of spectroscopic parameters. Abstract: The high resolution infrared spectra of CD 4 were measured with a Bruker IFS125 HR Fourier transform infrared spectrometer at an optical resolution of 0.003 cm − 1 and analyzed in the region of 800–1400 cm − 1 where the ν 2 / ν 4 dyad is located. The number of 3633 and 1927 transitions with J max = 31 and J max = 28 were assigned to the ν 4 and ν 2 bands of CD 4 (which is more than three times higher in comparison with the number of assigned transitions known in the literature). The subsequent weighted fit of experimentally assigned transitions was made with the Hamiltonian model which takes into account the resonance interactions between the upper ( 0001, F 2 ) and the ( 0100, E ) vibrational states. As a result, a set of 52 fitted parameters (10 parameters of the ground vibrational state, 19 parameters of the ( 0001, F 2 ) vibrational state, 9 parameters of the ( 0100, E ) vibrational state, and 14 resonance interaction parameters) was obtained which reproduces the positions of the initial 5560 experimental ro–vibrational transitions with the d rms = 1.83 × 10 − 4 cm − 1 which is close to the experimental uncertainty of the recorded spectra and is about 615 times better in comparison with the reproduction of the same 5560 transition values by the use of parameters from ( J . M o l . S p e c t r o s c ., 99, 63 − 86 ( 1983 ) ). A list of assigned transitions in the studied region is presented as the Supplementary material to this paper.